Aging and Executive Functioning: A Training Study on Focus-Switching - Dorbath, Lara; Hasselhorn, Marcus; Titz, Cora (Frontiers in Psychology, 2011)
Many studies suggest that age differences in a variety of cognitive tasks are due to age-related changes in executive control processes. However, not all executive control processes seem to be age-sensitive. Recently, Verhaeghen and colleagues (e.g., Verhaeghen et al. 2005) described dissociable age effects in an executive control process responsible for the switching of representations between different functional units of working memory. This so called focus-switching process has two components: (1) the switching of representations from an activated part of long-term memory into a region of immediate access (focus of attention) and (2) the maintenance of representations outside the focus of attention. Age-related deficits occurred in maintaining representations outside the focus of attention, but were absent in switching representations into and out of the focus of attention (e.g., Dorbath and Titz 2011). In the present study we applied a training approach to examine age-related differences in the trainability of maintenance and switching. We investigated 85 younger (age 19-35, M=24.07, SD=3.79) and 91 older (age 59-80, M=66.27, SD=4.75) adults using a continuous counting task in a pretest-training-posttest design. The participants were assigned to one of four training conditions differing in the demand to switch or to maintain. The results suggest the influence of training in both components of focus-switching for both, younger and older adults. However, age differences in the amount of training gains were observed. With respect to maintenance the results indicate a compensatory effect of training for older adults who improved their performance to the level of younger adults. With respect to switching, younger adults benefitted more from training than older adults. Trainability is thus reduced in older adults with respect to switching, but not for maintenance.